Success Factors of Standardized International Communication Campaigns - Bahles, Michael (2018)
The thesis aims to identify the success factors of standardized international communication campaigns. The main research objective is to examine how standardized international communication campaigns can be developed successfully. For this, the subject of standardized international communication campaigns is holistically examined. In order to analyze the topic thoroughly and in-depth, mostly qualitative and explorative research methods are used as case studies, expert interviews and an in-depth psychological research. The thesis will provide a summary of factors of how standardized international communication campaigns can be successful and a prototypical development process of standardized international communication campaigns. The research showed that standardized international communication campaigns can be effective and therefore successful. The analyzed cases proved certain successful standardized international communication campaigns and identified general success factors. The expert interviews with international marketing experts indicated that for the development a clear process is needed and that international stakeholders should be involved in the process. The interviews with international diplomats helped to find ways how the collaboration can happen more successfully. Conducting research is very important in the development of standardized international communication campaigns: As fundamental research in order to identify an universal consumer insight as well as testing of different campaign development stages. For the practical application of the overall research results, an own psychological research was conducted in order to identify fundamental motives for owning a car in the young target group in several countries.